Numbers, composition and distribution of populations of Anatidae wintering in West Africa - Roux, F; Jarry, G (Wildfowl, 1984)
Following 12 years of regular winter observations in the delta of the Sngal and the Niger flood zone in Mali, the first practically complete aerial survey of the wetlands of West Africa (Sngal, Niger, Volta and Chad Basins) was carried out in January 1984 during a period of exceptional drought. It revealed the hitherto unsuspected potential of Lake Chad (700,000 Anas sp.). It shows the overall size of the Anatidae populations of West Palearctic (essentially 440,000 Pintail Anas acuta and 900,000 Garganey A. querquedula) and Afro-tropical origin (70,000 Fulvous Whistling Ducks Dendrocygna bicolor, 110,000 White-faced Whistling Ducks D. viduata, 10,000 Comb Ducks Sarkidiornis melanotos and 10,000 Spur-winged Geese Plectropterus gambensis), which winter in this part of the African continent and their concentration (95%) on only 18 sites or groups of sites. A comparison with earlier data shows that the same sites are always occupied, whatever the water conditions. The effect of the drought is illustrated by a very notable decrease in numbers of both faunal groups in the Sngal delta (in favour of the lakes in southern Mauritania) and in the Niger Basin where a decrease of 500,000 individuals was recorded. The two hypotheses to be retained are: firstly, a decrease in overall population size (which is certain for the Afro-tropical species, and considerable for some of them); and secondly a movement to the east by Palearctic species, particularly towards the Chad Basin (which alone held more than half of the numbers counted) but perhaps also towards the Nile Valley in Sudan. It can be seen that even in these conditions of extreme drought, Palearctic and Afro-tropical Anatidae do not extend southwards beyond the Sahelian wetlands. These habitats, and among them the 18 sites traditionally exploited by Anatidae, therefore assume major importance for the survival of these populations and must be given priority in conservation measures and ecological research.